El concepto de racionalidad en los estudios sociales agrarios - Liceaga, Gabriel (2021)
In this paper we question the concept of rationality providing a possible use of it in social agrarian studies and economic anthropology. First, we theoretically clarify the path by relating and distinguishing at the same time two concepts: «modern rationality» and «economic rationality». Afterwards, we present some theoretical-methodological mediation that allows a categorical use of those concepts. Then, we elaborate some epistemological reflections on this matter. As a conclusion, we review our main contributions, emphasizing the link between general concerns, linked to the development of Modernity, with some of its historical embodiments in the agrarian order and economic anthropology.